PEDAGOGICAL ACTIVITY OF A MODERN TEACHER IN ORGANIZING LOCAL HISTORY WORK WITH STUDENTS: ESSENCE, STRUCTURE, LEVELS OF PROFESSIONALISM - O.S. Tsokur (Academy of Cognitive and Natural Sciences, 2009)
The article is dedicated to the subject , structure and levels of the professionalism of modern teacher's activity concerning the organization of the country studies work with pupils from the viewpoint of theory of pedagogical acmeology and pedagogical management. Certain attention is paid to the aspects concerning the preparing of the teacher to the activities of this kind.